STIGMATIZATION AND PUBLIC HEALTH ETHICS - Courtwright, Andrew (Bioethics, 2013)
Encouraged by the success of smoking denormalization strategies as a tobacco-control measure, public health institutions are adopting a similar approach to other health behaviors. For example, a recent controversial ad campaign in New York explicitly aimed to denormalize HIV/AIDS amongst gay men. Authors such as Scott Burris have argued that efforts like this are tantamount to stigmatization and that such stigmatization is unethical because it is dehumanizing. Others have offered a limited endorsement of denormalization/stigmatization campaigns as being justified on consequentialist grounds; namely, that the potential public health benefits outweigh any stigmatizing side effects. In this paper, I examine and reject the blanket condemnation of stigmatization efforts in public health. I argue that the moral status of such efforts are best evaluated within a contractualist, as opposed to a consequentialist, framework. Contractualism in public health ethics asks whether a particular stigmatizing policy could be justified to reasonable individuals who do not know whether they will be affected by that policy. Using this approach, I argue that it is sometimes permissible for public health institutions to engage in health-related stigmatization.